Patience Education Message in Story of Ibrahim and Ismail in Asshoffat: 99-108 - Imam Bahroni; Intan Indah Sari (Educan : Jurnal Pendidikan Islam, 2018)
Patience and obedience in the story of the Prophets Ibrahim and Ismail had an effect on Islamic Education, because they been able to run and do God's command with sincerity, patience, without any doubt and complaints in the heart. The purpose of this discussion is to know the effect of education on patience in the story of Prophet Ibrahim and Ismail. This type of research is literature of view, while in the analysis using Descriptive Analytical Method and Content Analytical Method. The patience in Islamic Education in the story of Ibrahim and Ismail includes: 1. The patience and the obedience will lead men to live happily in the world and the hereafter, 2. The deliberation will result in agreements that have been agreed by many parties, 3. The patience and the obedience will making a very confident heart to God's commandments, 4. A servant's love for His Lord beyond all else in the world on the basic of patience and obedience.